Biosurfactant-assisted bio-electrokinetic enhanced remediation of heavy metal-contaminated soil - Narenkumar, Jayaraman; Das, Bhaskar; Abilaji, Subramani; Sathishkumar, Kuppusamy; AlSalhi, Mohamad S.; Devanesan, Sandhanasamy; Rajasekar, Aruliah; Malik, Tabarak (Frontiers in Microbiology, 2024)
Background: Environmental soil contamination is a serious problem for human worldwide as it causes many diseases. Methods: The present study concentrates on utilizing biosurfactants produced by P. stutzeri NA3 and B. cereus EN6 as an electrolyte for removing chromium from contaminated soil using the electrokinetic process. Results: As a result, biosurfactants produced by P.stutzeri NA3 and B. cereus EN6 being a lipopeptide increases heavy metal mobility in the EK process. The chromium removal efficiency of a novel electrolyte (biosurfactants) in the EK process was compared with that of NA3 and EN6 biosurfactants.The EK results revealed a maximum chromium removal of 75% and 70% by NA3 and EN6, respectively, at the end of 7 days. Discussion: The biosurfactant aids in the breaking down of the heavy metals that are present deeper into the soil matrix. From the Metagenomics analysis it was identified that biosurfactant changes the microbial community with an enhanced ability to remove heavy. The phytotoxicity assay confirms that NA3 biosurfactant solution showed 95% seed germination and it has the ability to lower hazardous pollutants in the soil. Conclusion: The application of biosurfactant as potent electrolyte for remediation of hazardous pollutants in integrated process. Overall, the results of this study suggest that biosurfactant can serve as an economical and efficient electrolyte in the EK process to remove chromium from polluted soil.